MAPPING OF SOCIAL HARMONY AND VULNERABILITY OF RELIGIOUS PEOPLES (Case Study: Tombil Village, South Abad District, Alor Regency) - Noni Libertina Mokoil; Herman Utang; Susana Pellu (Jurnal Pluralis, 2024)
Harmony between religious communities in Tombil Village not only functions as a regulator of social relations but also as a mechanism to reduce social vulnerability. Adaptation to differences, achieving common goals, integration through collaboration, and maintaining cultural values ​​are important elements in maintaining social stability amidst diversity. Although challenges remain, an adaptive and integrative social structure strongly supports the maintenance of harmony in society